Factors Associated With All-Cause Mortality Among Patients With Multidrug-Resistant Tuberculosis—United States, 1993–2013. (29th July 2017) - Salinas, Jorge L; Armstrong, Lori R; Silk, Benjamin J; Haddad, Maryam B; Cegielski, J Peter
Abstract: We assessed characteristics associated with all-cause mortality among US patients with multidrug-resistant tuberculosis. Mortality decreased from 31% during 1993–2002 to 11% during 2003–2013. Directly observed therapy coverage increased from 74% to 95% and was protective against all-cause mortality after accounting for demographics, clinical characteristics, human immunodeficiency virus status, and period of treatment.